Berita Pustaka as historical source of Bandung Institute of Technology Library in 1970’s - Frial Ramadhan Supratman (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the Study: History of Indonesian library is less explored field in library studies. Debates on history of Indonesian library seems to be unexplored due to pressure on librarian to adapt with technological changes. It causes development of history of Indonesian library seems stagnant among scholars of library science and librarians. Meanwhile, in the field of history itself, library history is less attractive for historians. The development of historiography since 1980’s is more concerned with social movement history, though library played significant role in the field of education and research in Indonesia. Almost all research centers and universities certainly need library for obtaining references. Purpose: This article observes one of National Library of Indonesia’s rare collection named Berita Pustaka. The collection is a tabloid published by Center Library of Bandung Institute of Technology (ITB) in 1970’s. Today the collection is still deposited in Rare Newspaper Division, National Library of Indonesia with call number QQ-131. Method: In this article author uses qualitative method along with deep analysis of Berita Pustaka. Therefore, author also uses historical approach as a methodology in this article. Finding: In addition, the collection also contains information regarding library service for faculty members and students in 1970’s. Conclusion: Author argues that Berita Pustaka is an information source for researching history of Indonesian library, particularly higher education library.